Psychometric properties of the Turkish version of the Emotional Eating Scale for children and adolescents. (August 2016) - Bektas, Murat; Bektas, Ilknur; Selekoğlu, Yasemin; Kudubes, Aslı Akdeniz; Altan, Sema Sal; Ayar, Dijle
Abstract: This methodological-descriptive-sectional study was performed to assess the validity and reliability of the "Emotional Eating Scale Adapted for Use in Children and Adolescents (EES-C)" scale in Turkey. The sample group of the study was composed of 576 children and adolescents. The data were obtained by using the demographic data collection form and "Emotional Eating Scale Adapted for Use in Children and Adolescents (EES-C)". Cronbach's alpha values for the scale and its subscales were 0.90, 0.86, 0.76 and 0.71; respectively. Item-total correlations for the scale changed between 0.57 and 0.99 (p < 0.001). The indices of Model Fit were determined to be Root Mean Square Error of Approximation (RMSA) = 0.051, Goodness of Fit Index (GFI) = 0.91 and Comparative Fit Index (CFI) = 0.97. According to our results, it has been shown that the scale is a valid/reliable instrument to detect the emotional eating of Turkish children and adolescents. EES-C is a convenient tool for professionals to manage and prevent the emotional eating problems. Highlights: The scale is a valide instrument to detect the emotional eating of Turkish children and adolescents. The scale is a reliable instrument to detect the emotional eating of Turkish children and adolescents. EES-C is a convenient tool for professionals to manage and prevent the emotional eating problems.